When it's the slaves that pay: In search of a fair due diligence cost distribution in conflict mineral supply chains. (August 2022) - Schleper, Martin C.; Blome, Constantin; Stevenson, Mark; Thürer, Matthias; Tusell, Iu
Highlights: Cost-sharing mechanisms for sustainability need to be contextualized to avoid unintended consequences. Current due diligence schemes have limited effect call for alternative financing mechanisms in supply chains. The bottom up view for cost-sharing mechanisms for sustainability is required so that upstream suppliers aren't squeezed by more powerful supply chain players downstream. Cost-sharing mechanisms have salient implications for the design of modern slavery legislation. Abstract: Modern slavery and conflict minerals are often treated as two separate grand challenges governed by different legislation, yet conflict mineral settings commonly involve and inflict slavery in supply chains – hence these two wicked problems are deeply interconnected. This paper focuses on due diligence in the context of conflict mineral supply chains, and in doing so provides important insights for modern slavery in general. Using more than 38 h of recordings from exploratory interviews with 46 experts from 43 organizations, our study investigates: a) how due diligence costs and benefits are actually distributed in supply chains in practice; and b) the means through which due diligence costs and benefits can be (more appropriately) shared. We find that there is a lack of contextualization of cost-sharing mechanisms to conflict mineral supply chains, with most mechanisms being imported from the standard business literature where the producer must pay the production costs before reaping the benefits that offset these costs. But in conflict mineral supply chains, these benefits often do not materialize for the producer and, consequently, cost-sharing mechanisms lead to unintended consequences. The findings question the usefulness of due diligence, call for alternative financing mechanisms, and for contextualized solutions designed from the bottom up. This in turn has important implications for enhancing legislation on modern slavery.